Methodology For Developing Analytical Thinking Of Future Physics Teachers Based On A Dialectic Approach (Journal of Pedagogical Inventions and Practices, 2025)
The development of analytical thinking is a central component in preparing competent and reflective physics teachers. This article proposes a methodology grounded in the dialectic approach to foster analytical thinking among pre-service physics teachers. It explores how dialectical reasoning—through contradiction, synthesis, and transformation—can serve as a philosophical and pedagogical foundation for structuring physics education. The study emphasizes integrative strategies such as reflective problem-solving, historical analysis of scientific ideas, and dynamic modeling. The approach supports future teachers in cultivating logical rigor, conceptual clarity, and critical thinking necessary for the teaching profession in the 21st century